Ultrasound-detected musculoskeletal urate crystal deposition: which joints and what findings should be assessed for diagnosing gout?. Issue 8 (24th May 2013) - Naredo, Esperanza; Uson, Jacqueline; Jiménez-Palop, Mercedes; Martínez, Agustín; Vicente, Esther; Brito, Elia; Rodríguez, Ana; Cornejo, Francisco Javier; Castañeda, Santos; Martínez, María Jesús; Sanz, Jesús; Möller, Ingrid; et al.
Abstract : Objective: The primary objective of this prospective case-control study was to assess the diagnostic value of several intra-articular and periarticular ultrasound (US)-detected abnormalities in the upper and lower limbs in gout. The secondary objective was to test the concurrent validity of US abnormalities using as gold standard the microscopic demonstration of monosodium urate (MSU) crystals. Methods: Ninety-one men with gout and 42 age-matched controls were prospectively recruited. All patients with gout and controls underwent US assessment of several US abnormalities in 26 joints, six bursae, eight tendons, 20 tendon compartments, four ligaments, and 18 articular cartilages by experts in US blinded to the patients' group. Patients with gout and controls with US abnormalities were asked to undergo US-guided aspiration for microscopic identification of MSU crystals. Interobserver and intraobserver reliability of the US assessment was evaluated in a web-based exercise. Results: The assessment of one joint (ie, radiocarpal joint) for hyperechoic aggregates (HAGs), two tendons (ie, patellar tendon and triceps tendon) for HAGs and three articular cartilages (ie, first metatarsal, talar and second metacarpal/femoral) for double contour sign showed the best balance between sensitivity and specificity (84.6% and 83.3%, respectively). Intraobserver reliability was good (mean κ 0.75) and interobserver reliability was moderate (κ 0.52). The aspirated material from HAGs was positive for MSU crystals in 77.6% of patients with gout and negative in all controls. Conclusions: Our results suggest that US bilateral assessment of one joint, three articular cartilages and two tendons may be valid for diagnosing gout with acceptable sensitivity and specificity.